2019
DOI: 10.1002/dneu.22716
|View full text |Cite
|
Sign up to set email alerts
|

Plasma metabolites related to cellular energy metabolism are altered in adults with Down syndrome and Alzheimer's disease

Abstract: Down syndrome (DS) is a well‐known neurodevelopmental disorder most commonly caused by trisomy of chromosome 21. Because individuals with DS almost universally develop heavy amyloid burden and Alzheimer's disease (AD), biomarker discovery in this population may be extremely fruitful. Moreover, any AD biomarker in DS that does not directly involve amyloid pathology may be of high value for understanding broader mechanisms of AD generalizable to the neurotypical population. In this retrospective biomarker discov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 104 publications
1
26
0
Order By: Relevance
“…The same process (impaired mitochondrial function, and the resulting compensatory upregulation of glycolysis) would also produce increases in systemic lactate production (again, a common observation in septic shock, where, in fact, elevated lactate levels are excellent predictors of mortality); indeed, our meta-analysis has clearly demonstrated that DS cells produce increased levels of lactate (Fig. 4 c) and clinical studies have also reported elevated plasma lactate levels in DS individuals (Caracausi et al 2018 ; Gross et al 2019 ).…”
Section: Implications Conclusion and Outlookmentioning
confidence: 52%
“…The same process (impaired mitochondrial function, and the resulting compensatory upregulation of glycolysis) would also produce increases in systemic lactate production (again, a common observation in septic shock, where, in fact, elevated lactate levels are excellent predictors of mortality); indeed, our meta-analysis has clearly demonstrated that DS cells produce increased levels of lactate (Fig. 4 c) and clinical studies have also reported elevated plasma lactate levels in DS individuals (Caracausi et al 2018 ; Gross et al 2019 ).…”
Section: Implications Conclusion and Outlookmentioning
confidence: 52%
“…If lower UCK2 mRNA levels in different brain regions correspond with a decrease in pyrimidine synthesis pathway, and, as it has been recently reported, AD subjects show lower uridine concentrations in plasma and cerebrospinal fluid [5559], then AD patients probably have a cerebral deficiency in many cellular functions related to the metabolism of uridine. Therefore, it can be suggested that uridine therapeutic administration would improve biochemical pathways related to brain function.…”
Section: Resultsmentioning
confidence: 93%
“…Formimidoyltransferase cyclodeaminase (FTCD) is another gene located on the long arm of HSA21, which encodes an enzyme that participates in histidine and folate metabolism, both essential for purine, pyrimidines, and amino acids biosynthesis. In addition, aberrant metabolism of adenosine, homocysteine, and folate was also observed in DS (Patterson, 2009;Gross et al, 2019).…”
Section: Down Syndrome As a Metabolic Diseasementioning
confidence: 99%
“…With regard to brain alterations, accumulation of toxic catabolites (Caracausi et al, 2018;Gross et al, 2019) or dysfunction of key metabolic pathways were identified as crucial determinants triggering neuronal dyshomeostasis and neurodegeneration in DS (Head et al, 2018;Lott and Head, 2019;Vacca et al, 2019).…”
Section: Brain Insulin Resistance Is a Feature Of Down Syndromementioning
confidence: 99%